Abstract 10154: Efficacy of the New Calpain Inhibitor Npo2270 Compared with Enalapril in Mouse Models of Ventricular Remodeling and Heart Failure - Aluja, David; Delgado-Tomas, Sara; Llenas, Jesus; Vazquez, Enrique; INSERTE, Javier (Circulation (New York, N.Y.), 2021)
IntroductionCa2+-dependent proteases calpains contribute to adverse ventricular remodeling and heart failure (HF) in multiple experimental models. However, the efficacy of pharmacological calpain inhibition for treating HF in patients has not yet been tested mainly due to the limitations of available inhibitors. Hypothesis:To assess the effect of NPO-2270, a new ketoamide derivative with calpain inhibitory properties, against myocardial remodeling and HF, and compare its effectiveness with enalapril. MethodsC57BL6/J mice were subjected to transverse aortic constriction (TAC) for 28 days or to coronary occlusion for 45 min followed by 21 of reperfusion (IR). NPO-2270 and enalapril were orally administered once a day at 10 mg/Kg/day, starting 7 days after TAC surgery or at the onset of reperfusion. Echocardiographic data, markers of hypertrophy, fibrosis, calpain activity and calpain substrates were measured at different time points. ResultsTAC and IR increased calpain expression and activity. Chronic oral administration of NPO-2270 and enalapril prevented progression of hypertrophy and interstitial fibrosis induced by TAC, and reduced scar area by 40% in mice subjected to IR with no significant differences between treatments. However, NPO-2270 attenuated myocardial dysfunction to a greater extent than enalapril in both experimental models (27% of EF reduction in the control group, 6% in NPO-2270 group and 16% in the enalapril group subjected to TAC, P=0.024 between NPO-2270 and enalapril groups; and 11.9% in the control group, 1.8% in NPO-2270 group and 8.8% in the enalapril group subjected to IR, P=0.160 between NPO-2270 and enalapril groups). These results correlated with better preservation of cell adhesion complex in the group treated with NPO-2270. ConclusionsOur data demonstrate that the calpain inhibitor NPO-2270 prevents the progression of hypertrophy and fibrosis with similar efficacy to enalapril but ameliorates cardiac dysfunction more effectively in two clinically relevant experimental models of HF. This study provides compelling evidence that the new calpain inhibitor NPO-2270 is an attractive candidate to determine the potential of calpain inhibition as a strategy for treating HF in patients.